Targetable kinase gene fusions in high-risk B-ALL: a study from the Children's Oncology Group - Reshmi, Shalini C; Harvey, Richard C; Roberts, Kathryn G; Stonerock, Eileen; Smith, Amy; Jenkins, Heather; Chen, I-Ming; Valentine, Marc; Liu, Yu; Li, Yongjin; Shao, Ying; Easton, John; et al. (Blood, 2017)
Philadelphia chromosome-like (Ph-like) acute lymphoblastic leukemia (ALL) is a high-risk subtype characterized by genomic alterations that activate cytokine receptor and kinase signaling. We examined the frequency and spectrum of targetable genetic lesions in a retrospective cohort of 1389 consecutively diagnosed patients with childhood B-lineage ALL with high-risk clinical features and/or elevated minimal residual disease at the end of remission induction therapy. The Ph-like gene expression profile was identified in 341 of 1389 patients, 57 of whom were excluded from additional analyses because of the presence of - (n = 46) or - (n = 11). Among the remaining 284 patients (20.4%), overexpression and rearrangement of ( - or - ) were identified in 124 (43.7%), with concomitant genomic alterations activating the JAK-STAT pathway ( , , ) identified in 63 patients (50.8% of those with rearrangement). Among the remaining patients, using reverse transcriptase polymerase chain reaction or transcriptome sequencing, we identified targetable ABL-class fusions ( , , , and ) in 14.1%, rearrangements or fusions in 8.8%, alterations activating other JAK-STAT signaling genes ( , , ) in 6.3% or other kinases ( , , ) in 4.6%, and mutations involving the Ras pathway ( , , , ) in 6% of those with Ph-like ALL. We identified 8 new rearrangement partners for 4 kinase genes previously reported to be rearranged in Ph-like ALL. The current findings provide support for the precision-medicine testing and treatment approach for Ph-like ALL implemented in Children's Oncology Group ALL trials.